THE PUBLIC SPHERE AND CONTEMPORARY CHALLENGES: SOCIAL-PHILOSOPHICAL ANALYSIS - Shorina, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
The presence of a public sphere is a defining feature of all democratic societies. With the rise of commercialization, political intervention, and mass media, especially new media in the late 20th century, the nature of the public sphere has transformed. In our time, the public sphere is a contradictory and dynamic phenomenon, and the theoretical interpretations in its study are just as diverse. This is what determines the increased cognitive interest in its analysis.The aim and tasks are to briefly clarify the historical evolution in the socio-philosophical understanding of the public sphere, to explore the conditions of its recent transformation, and to formulate contemporary problems and challenges. Research methods. The theory and method of discourse analysis, the method of comparative analysis, as well as systemic-logical, dialectical, analytical, synthetic, and structural research methods are used.Research results. In a broad sense, the concept of the public sphere has its roots in ancient Greek philosophical thought and political democratic culture. In the 20th century, J. Habermas was the first to theoretically substantiate the concept of the public sphere as a space in which citizens could freely discuss public issues and criticize the government. Discussion. The introduction of new digital media communications forces us to reconsider the concept of the public sphere, exploring the profound shifts and problems that this space brings to democratic discourse. J. Habermas notes contradictory trends that indicate, on the one hand, the expansion of access to information and public openness, but at the same time, lead to the regression of democratic institutions and the degradation of public communication. Conclusions. Despite criticisms of metaphysicality and empirical inaccuracy from various critics, J. Habermas's concept of the public sphere retains much heuristic value. It performs a normative and regulatory role in social life, namely, it serves the cause of solidarization, and integration of people based on rational and collective values